Three-Dimensional Visualization of Tick-Borne Encephalitis Virus Infection in Mouse Brain Tissue - Gahbauer, Sarah (Jihočeská univerzita, 2023)
Tick-borne Encephalitis Virus (TBEV) is an important human pathogen that causes serious neuroinfections such as inflammation of the brain (encephalitis), the lining of the brain (meningitis), and the spinal cord (myelitis). The exact mechanism by which the virus enters the brain remains an unsolved problem. However, the virus is known to infect several cells in the brain, such as glial cells and neurons. This thesis focusses on the ultrastructural changes induced by infection in the mouse brain. A special focus was placed on the endothelium during infection and to determine if or how endothelial cells can be infected to reconstruct possible entry routes of the virus into the brain.
Three-Dimensional Visualization of Tick-Borne Encephalitis Virus Infection in Mouse Brain Tissue
Keywords: Tick borne encephalitis virus; Neuroinfections; Ultrastructural changes; Autophagy; Membranous whorls; Blood brain barrier; Tick borne encephalitis virus; Neuroinfections; Ultrastructural changes; Autophagy; Membranous whorls; Blood brain barrier